Hormonal status and age differentially affect tolerance to the disruptive effects of delta-9-tetrahydrocannabinol (Δ9-THC) on learning in female rats - Winsauer, Peter J.; Filipeanu, Catalin M.; Weed, Peter F.; Sutton, Jessie L. (Frontiers in Pharmacology, 2015)
The effects of hormone status and age on the development of tolerance to D9-THC were assessed in sham-operated (intact) or ovariectomized (OVX) female rats that received either intraperitoneal saline or 5.6 mg/kg of D9-THC daily from postnatal day (PD) 75 to 180 (early adulthood onward) or PD 35 to 140 (adolescence onward). During this time, the 4 groups for each age (i.e., intact/saline, intact/THC, OVX/saline, and OVX/THC) were trained in a learning and performance procedure and dose-effect curves were established for D9-THC (0.56-56 mg/kg) and the cannabinoid type-1 receptor (CB1R) antagonist rimonabant (0.32-10 mg/kg). Despite the persistence of small rate-decreasing and error-increasing effects in intact and OVX females from both ages during chronic D9-THC, all of the D9-THC groups developed tolerance. However, the magnitude of tolerance, as well as the effect of hormone status, varied with the age at which chronic D9-THC was initiated. There was no evidence of dependence in any of the groups. Hippocampal protein expression of CB1R, AHA1 (a co-chaperone of CB1R) and HSP90β (a molecular chaperone modulated by AHA-1) was affected more by OVX than chronic D9-THC; striatal protein expression was not consistently affected by either manipulation. Hippocampal BDNF expression varied with age, hormone status, and chronic treatment. Thus, hormonal status differentially affects the development of tolerance to the disruptive effects of delta-9-tetrahydrocannabinol (D9-THC) on learning and performance behavior in adolescent, but not adult, female rats. These factors and their interactions also differentially affect cannabinoid signaling proteins in the hippocampus and striatum, and ultimately, neural plasticity.